Operando XAFS Imaging of Distribution of Pt Cathode Catalysts in PEFC MEA. Issue 7 (30th October 2018) - Matsui, Hirosuke; Maejima, Naoyuki; Ishiguro, Nozomu; Tan, Yuanyuan; Uruga, Tomoya; Sekizawa, Oki; Sakata, Tomohiro; Tada, Mizuki
Abstract: Three‐dimensional imaging using X‐ray as a probe is state‐of‐the‐art for the characterization of heterogeneous materials. In addition to simple imaging of sample morphology, imaging of elemental distribution and chemical states provides advanced maps of key structural parameters of functional materials. The combination of X‐ray absorption fine structure (XAFS) spectroscopy and three‐dimensional imaging such as computed tomography (CT) can visualize the three‐dimensional distribution of target elements, their valence states, and local structures in a non‐destructive manner. In this personal account, our recent results on the three‐dimensional XAFS imaging for Pt cathode catalysts in the membrane electrode assembly (MEA) of polymer electrolyte fuel cell (PEFC) are introduced. The distribution and chemical states of Pt cathode catalysts in MEAs remarkably change under PEFC operating conditions, and the 3D XAFS imaging revealed essential events in PEFC MEAs. Abstract : Three‐dimensional imaging using X‐ray as a probe is state‐of‐the‐art for the characterization of heterogeneous solid materials. In this Personal Account, our recent results on the three‐dimensional XAFS imaging for Pt cathode catalysts in the membrane electrode assembly (MEA) of polymer electrolyte fuel cell (PEFC) are introduced.